2019
DOI: 10.1177/0954411919881526
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial pressure–based validation and analysis of traumatic brain injury using a new three-dimensional finite element human head model

Abstract: Traumatic brain injuries are life-threatening injuries that can lead to long-term incapacitation and death. Over the years, numerous finite element human head models have been developed to understand the injury mechanisms of traumatic brain injuries. Many of these models are erroneous and used ellipsoidal or spherical geometries to represent brain. This work is focused on the development of high-quality, comprehensive three-dimensional finite element human head model with accurate representation of cerebral su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
3
8
0
Order By: Relevance
“…For instance, Willinger et al [45], Zhao et al [21], and Mao et al [15] observed peak-pressure discrepancies of less than 19% and temporal phase-shift differences of less than 1.3 ms. The peak-pressure discrepancy in the third ventricle (33.7%) was also comparable to the values reported by Zhao et al and Khanuja and Unni [12], who observed a peak-pressure discrepancy equivalent to 32%. We applied the force derived from the measured acceleration on the model forehead, similar to the study by Khanuja and Unni, which resulted in a difference of 41% between the simulated and experimental ICP values in the occipital lobe.…”
Section: Model Validationsupporting
confidence: 89%
See 3 more Smart Citations
“…For instance, Willinger et al [45], Zhao et al [21], and Mao et al [15] observed peak-pressure discrepancies of less than 19% and temporal phase-shift differences of less than 1.3 ms. The peak-pressure discrepancy in the third ventricle (33.7%) was also comparable to the values reported by Zhao et al and Khanuja and Unni [12], who observed a peak-pressure discrepancy equivalent to 32%. We applied the force derived from the measured acceleration on the model forehead, similar to the study by Khanuja and Unni, which resulted in a difference of 41% between the simulated and experimental ICP values in the occipital lobe.…”
Section: Model Validationsupporting
confidence: 89%
“…3c) [15,51]. We did not constrain the neck of the FE model, consistent with previous studies [12,15,21,45]. We performed blunt loading simulations using ABAQUS/Explicit 2018 (Dassault Systèmes Simulia Corp., Johnston, RI) on ( 1 We post-processed the simulation results using EnSight 10.2.5a (Computational Engineering International, Inc., Apex, NC) and determined the intracranial pressure (ICP), the relative displacement (RD) between the brain and skull, the von Mises stress (VMS), and the maximum principal strain (MPS).…”
Section: Blunt Impact Simulationssupporting
confidence: 60%
See 2 more Smart Citations
“…Some of these models were developed with the goal to optimize the helmet design according to specific criteria [23,27,28,[30][31][32][33][34][35][36][37][38]. These coupled with FE head models make it possible to predict traumatic brain injuries [39][40][41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%